Pharmacovigilance study of the frequency of gastrointestinal ulceration reports associated with immune checkpoint inhibitors: insights from the FDA adverse event reporting system - Lei, Liqiang; Wang, Lifen; Shen, Sugang; Zhao, Ge; Zhao, Xingming; Dong, Honglin (Frontiers in Pharmacology, 2025)
BackgroundImmune checkpoint inhibitors (ICIs) have revolutionized the treatment landscape for cancer, yet they are linked to immune-related adverse events (AEs), one of which includes gastrointestinal ulceration (GU). The objective of this study was to evaluate the reporting frequency of GU reported in connection with ICIs by utilizing data from the United States (U.S.) Food and Drug Administration Adverse Event Reporting System (FAERS).Materials and methodsAEs pertaining to GU attributed to ICIs were extracted from the U.S. FAERS database for the time frame spanning from the fourth quarter of 2018 to the fourth quarter of 2024. A disproportionality analysis was performed employing the reporting odds ratio (ROR) and information component (IC), accompanied by 95% confidence intervals (95% CI). Beyond the disproportionality analysis, this investigation also examined gender disparities and the latency period for the onset of gastrointestinal AEs related to ICIs.ResultsA total of 1,415 adverse event reports regarding GU linked to ICIs as the primary suspect drug were collected. The occurrence of GU attributed to ICIs was observed to be more prevalent among males and older individuals. The principal countries reporting these events were Japan, the United States, and Germany, with Japan notably contributing the highest number of reports for Nivolumab and Pembrolizumab. A significant association was observed between the drugs Ipilimumab (ROR: 3.73 [3.14–4.44], IC: 1.89), Pembrolizumab (ROR: 3.08 [2.83–3.35], IC: 1.60), Atezolizumab (ROR: 4.10 [3.67–4.58], IC: 2.02), Nivolumab (ROR: 2.45 [2.23–2.69], IC: 1.28) and reports of GU. Conversely, Cemiplimab (ROR: 1.06 [0.55–2.05], IC: 0.09) did not exhibit a significant correlation. Among patients administered Pembrolizumab, the reporting frequency of intestinal perforation in females was considerably greater than that in males, presenting the most robust signal strength (ROR = 1.98 [1.28–3.05], P < 0.01).ConclusionThis study presents the most current real-world evidence regarding the safety profile of ICIs therapy in relation to GU, highlighting variations among different ICIs and between genders. It is imperative for healthcare providers to maintain heightened awareness of potential GU adverse events associated with ICIs and to implement timely preventive or therapeutic interventions to enhance the safety of ICIs in clinical practice.